2012
DOI: 10.1371/journal.pone.0045967
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression Analysis and Prognostic Value of BLCAP in Breast Cancer

Abstract: Bladder Cancer Associated Protein (BLCAP, formerly Bc10), was identified by our laboratory as being down-regulated in bladder cancer with progression. BLCAP is ubiquitously expressed in different tissues, and several studies have found differential expression of BLCAP in various cancer types, such as cervical and renal cancer, as well as human tongue carcinoma and osteosarcoma. Here we report the first study of the expression patterns of BLCAP in breast tissue. We analyzed by immunohistochemistry tissue sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Among these 10 genes, PAK3 and IL15RA were previously shown to be involved in PCa progression [ 52 , 53 ], and PAK3 was identified as an epigenetic biomarker for the prognostic diagnosis of PCa [ 52 ]. Despite the fact that no reports on the association of the remaining genes with PCa were found, these genes were shown to be associated with the progression of other cancers, such as breast cancer [ 54 ] pancreatic cancer [ 55 ] and leukemia [ 56 ]. These evidences support that miR-648 could be involved in PCa and act as a novel molecular biomarker for PCa diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among these 10 genes, PAK3 and IL15RA were previously shown to be involved in PCa progression [ 52 , 53 ], and PAK3 was identified as an epigenetic biomarker for the prognostic diagnosis of PCa [ 52 ]. Despite the fact that no reports on the association of the remaining genes with PCa were found, these genes were shown to be associated with the progression of other cancers, such as breast cancer [ 54 ] pancreatic cancer [ 55 ] and leukemia [ 56 ]. These evidences support that miR-648 could be involved in PCa and act as a novel molecular biomarker for PCa diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue microarrays (TMAs) were purchased from Pantomics (BRC961, BRC962 BRC1501, BRC1502, BRC1503), Richmond, CA, USA). Additional tissue samples of normal breast tissue were produced and processed as previously published 57 . FFPE cell-blocks were prepared as in Cabezon et al 58 .…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers reported that overexpression of BLCAP induced cell growth inhibition and apoptosis, suggested that BLCAP may function as a potential tumor suppressor in carcinogenesis through regulating cell proliferation and survival [ 4 6 ]. In addition, BLCAP represented a negative correlation with tumor progression by comparing its expression pattern in different grades and stages of bladder cancer and breast cancer, suggesting that it might be of value as a biomarker and providing a new perspective for the clinical application of this protein [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%